## Understanding (9/7)^-2 without Exponents

The expression (9/7)^-2 might look intimidating at first glance, but it's actually quite straightforward once you understand the rules of exponents. Let's break it down:

### Negative Exponents

A negative exponent means we take the **reciprocal** of the base raised to the **positive** version of the exponent. In our case:

(9/7)^-2 = 1 / (9/7)^2

### Fractions to a Power

Now we have to deal with (9/7)^2. Raising a fraction to a power means we raise both the numerator and denominator to that power:

(9/7)^2 = 9^2 / 7^2

### Calculating the Squares

Finally, we calculate the squares:

9^2 = 9 * 9 = 81 7^2 = 7 * 7 = 49

### Putting it all Together

Now we can substitute everything back into our original expression:

(9/7)^-2 = 1 / (9/7)^2 = 1 / (9^2 / 7^2) = 1 / (81/49)

Since dividing by a fraction is the same as multiplying by its reciprocal:

1 / (81/49) = 1 * (49/81) = **49/81**

Therefore, (9/7)^-2 is equivalent to 49/81 without using exponents.